Against Modern Football: Mobilising Protest Movements in Social Media. (August 2018) - Hill, Tim; Canniford, Robin; Millward, Peter
Recent debates in sociology consider how Internet communications might catalyse leaderless, open-ended, affective social movements that broaden support and bypass traditional institutional channels to create change. We extend this work into the field of leisure and lifestyle politics with an empirical study of Internet-mediated protest movement, Stand Against Modern Football . We explain how social media facilitate communications that transcend longstanding rivalries, and engender shared affective frames that unite diverse groups against corporate logics. In examining grassroots organisation, communication and protest actions that span online and urban locations, we discover sustained interconnectedness with traditional social movements, political parties, the media and the corporate targets of protests. Finally, we suggest that Internet-based social movements establish stable forms of organisation and leadership at these networked intersections in order to advance instrumental programmes of change.